Cove-Edged Graphene Nanoribbons with Incorporation of Periodic Zigzag-Edge Segments - Wang, Xu; Ma, Ji; Zheng, Wenhao; Osella, Silvio; Arisnabarreta, Nicolas; Droste, Jorn; Serra, Gianluca; Ivasenko, Oleksandr; Lucotti, Andrea; Beljonne, David; Bonn, Mischa; Liu, Xiangyang; et al. (Journal of the American Chemical Society, 2022)
Structurally precision graphene nanoribbons (GNRs) are promising candidates for next-generation nanoelectronics due to their intriguing and tunable electronic structures. GNRs with hybrid edge structures often confer them unique geometries associated with exotic physicochemical properties. Herein, a novel type of cove-edged GNRs with periodic short zigzag-edge segments is demonstrated. The bandgap of this GNR family can be tuned using an interplay between the length of the zigzag segments and the distance of two adjacent cove units along the opposite edges, which can be converted from semiconducting to nearly metallic. A family member with periodic cove-zigzag edges based on N = 6 zigzag-edged GNR, namely 6-CZGNR-(2,1), is successfully synthesized in solution through the Scholl reaction of a unique snakelike polymer precursor (10) that is achieved by the Yamamoto coupling of a structurally flexible S-shaped phenanthrene-based monomer (1). The efficiency of cyclodehydrogenation of polymer 10 toward 6-CZGNR-(2,1) is validated by FT-IR, Raman, and UV-vis spectroscopies, as well as by the study of two representative model compounds (2 and 3). Remarkably, the resultant 6-CZGNR-(2,1) exhibits an extended and broad absorption in the near-infrared region with a record narrow optical bandgap of 0.99 eV among the reported solution-synthesized GNRs. Moreover, 6-CZGNR-(2,1) exhibits a high macroscopic carrier mobility of ∼20 cm2 V-1 s-1 determined by terahertz spectroscopy, primarily due to the intrinsically small effective mass (m*e = m*h = 0.17 m0), rendering this GNR a promising candidate for nanoelectronics.
CRIS-Team Scopus Importer:2023-03-20